Gender segregation and the wage gap in Portugal: an analysis at the establishment level - Portela, Miguel (2005)
Using a large linked employer-employee data set, this paper aims at quantifying the trend in worker segregation at the establishment level and its impact on wages in Portugal over a fifteen year period. We concentrate on the gender dimension, to answer the questions: What is the level of gender segregation across establishments in the Portuguese labor market and how has it evolved over time? What is the impact of segregation on wages? Is that impact different for men and women? Systematic and random components of segregation are computed. We use standard wage decomposition techniques to evaluate the impact of the composition of the labor force at the establishment level on wages. The results reveal a high degree of systematic gender segregation. A higher proportion of females in the establishment lowers females´ wages while, on the contrary, it raises males´wages. The evidence gathered is consistent with the taste-based model of employer behavior and with the theory of sorting of workers across establishments based on their productivity.